Fisheries Management of Mexican and Central American Estuaries - Amezcua, Felipe; Bellgraph, Brian (Estuaries of the World, 2014)
The tropical estuarine systems of Mexico and Central America are an important part of the region´s coastlines; for example Mexico alone possesses more than 770 thousand hectares of mangroves, as well as the largest estuarine mangrove complex on the American Pacific (Marismas Nacionales), yet is one of the poorest studied areas in the world. This is the first book that deals extensively with fisheries management issues in this region from physical-chemistry, ecological and socioeconomic views, providing an understanding on the function and the effects of human activities on these areas, with works undertaken by local scientist.